Relationship between land uses and diversity of dung beetles (Coleoptera: Scarabaeinae) in the southern Atlantic forest of Argentina: which are the key factors? - Giménez Gómez, Victoria Carolina (2018)
Fil: Giménez Gómez, Victoria Carolina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Nordeste; Argentina.